Les effets ambivalents des héritages dans la reconversion des anciens territoires nucléaires - Belinda Ravaz; Teva Meyer; Pierre-Henri Bombenger; Brice Martin; Massimiliano Capezzali (VertigO)
Across the world, 165 reactors have been permanently shut down and more than one hundred are expected to be decommissioned in the near futur. Many regions will therefore be faced with the issue of land redevelopment. Many papers addressing the socio-economic impact of closing nuclear sites have underlined the opposition triggered by the disappearance of nuclear activities. However, few studies have focused on the redevelopment of the land this entails. This article addresses the effects of redeveloping the land through the reconversion process of two nuclear power plants: Brunsbüttel in Germany and Barsebäck in Sweden. The closure and reconversion of the German plant seems to have stirred little debates on the local level concerning social and land redevelopment issues. To the contrary, the Swedish plant led to much socio-political polemic and controversies regarding its reconversion. A comparison of the territorial outcome of these two fundamentally different nuclear power plants contributes to enrich the discussion on the factors that impact the post-nuclear outcome of land redevelopment.